Impact of rising world rice prices on poverty and inequality in Burkina Faso - Badolo, F.; Traoré, Fousseini (Wiley, 2015)
Between January 2006 and April 2008, the prices of most agricultural products rose considerably in international markets. Empirical studies show that this spike in world food prices increased the number of poor households in developing countries, but the extent was not the same in all countries. This article assesses the impact of rising rice prices on poverty and income inequality in Burkina Faso, using a methodology based on the concept of compensating variation combined with the net benefit ratio (NBR) developed by Deaton (1989) and a living standard survey (QUIBB, 2003). The results show that higher prices have a negative impact on income and poverty in the regions with a large proportion of households that are net buyers of rice. The poverty rate increases by 2.2 to 2.9 percentage points depending on the assumptions, the increase being higher in urban areas than in rural areas. Rising rice prices also increase income inequality, which increases particularly in urban areas and in relatively rich regions, but decreases in poor regions with a large proportion of rice producers.